Modulatory mechanism of the paraventricular thalamus (PVT) under general anesthesia - Li, Jia; Wei, Yiyong; Zhang, Donghang (Frontiers in Pharmacology, 2026)
The paraventricular thalamus (PVT) is a critical brain region involved in controlling sleep-wakefulness. Many neural nuclei and circuits regulate consciousness under both sleep-wakefulness and general anesthesia, suggesting that a common neural mechanism contributes to these two conditions. Recently, accumulating evidence has revealed that the activities of the PVT are associated with the actions of both volatile and intravenous general anesthetics. However, there is divergence regarding neuronal types, circuits, or different anesthesia periods. Herein, we reviewed the current literature and summarized the role of PVT in general anesthesia, which provides a better understanding of the modulatory mechanism of PVT on the actions of general anesthetics.